PENGARUH TAX PLANNING, DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERATING - Ayem, Sri; Anggara, B. Krisnandi Surya (Jurnal Akuntansi, 2023)
This research was conducted to see whether tax planning has a positive effect on earnings management, to determine whether leverage has a negative effect on earnings management, to determine whether managerial ownership strengthens or weakens the influence between tax planning and earnings management and also to determine whether managerial ownership strengthens or weaken the influence between leverage and yield management. In this study, the collection, processing, analysis, and presentation of data are carried out systematically and objectively to solve a problem or test a hypothesis to develop general principles. Based on the results it was concluded that tax planning has a positive effect on earnings management, leverage has a positive effect on earnings management, the higher the company's leverage level, the higher the company's potential to manage earnings. management ownership variables weaken the impact of tax planning on income management. Tax planning is one way that is used by taxpayers in managing their business or income taxation. Leverage does not affect earnings management, because companies that have a high level of leverage due to total debt to total assets face the risk of not being able to meet debt repayments